The Effect of Project Based Learning Model on High School Physics Learning - Fitriani, Nining; Apsari, Putu Ayas Ditha; Hayati, Saadila Hayati; Yulianti, Sri; Sukmawati, Sukmawati; Wati, Widia; Istiarini, Yunita (Balai Publikasi Indonesia, 2022)
This study aims to determine the effect of the PjBL (Project Based Learning) learning model on high school physics learning. The problem that often arises in the world of education is the weak ability of students to use their thinking skills to solve problems. Given that each student has a different learning style, PjBL (Project Based Learning) provides opportunities for students to explore content (material) using various means that are meaningful to themselves. The research method used is the research method and development (research and development / R&D) is a research method used to research so as to produce new products and then test the effectiveness of these products. The results of student learning using PjBL influence several things, such as creative thinking skills, elaboration, and even students can learn on their own without the help of others. Data collection in this study was carried out by observing and reviewing several journals through Google Scholar